Meta-analysis of the efficacy of camel milk consumption for improving autism symptoms in children in randomized clinical trials - Mahmoud Kandeel; Mohamed A. Morsy; Khalid M. Al Khodair; Sameer Alhojaily (Open Veterinary Journal)
Background: Camel milk has emerged as a potential complementary therapy for autism spectrum disorder (ASD). Aim: This study aimed to gather evidence from randomized controlled trials (RCTs) on the effectiveness of camel milk consumption in improving symptoms and associated measures in children with ASD. Methods: Comprehensive searches of multiple databases were conducted up to March 14, 2024, for RCTs that had evaluated whether camel milk consumption by children with ASD was more beneficial than the consumption of a control substance. Quality and bias analyses and meta-anlaysis data were synthesized and analyzed. Results: Of 136 records identified, 5 RCTs (n = 299 children) were selected. The mean difference in scores on the Childhood Autism Rating Scale (CARS) for the group given camel milk and the control groups was a mean deviation (MD) ‒0.75, 95% CI ‒1.97 to 0.47, p = .23. The mean difference in CARS scores in the subgroup analyses for raw camel milk was MD ‒0.95, 95% CI ‒2.33 to 0.44, p = .18 and boiled camel milk MD ‒0.50, 95% CI ‒1.93 to 0.93, p = .49. A qualitative synthesis found that raw camel milk intake led to improvements in various social behaviors in children with ASD. Camel milk consumption resulted in increased levels of anti-inflammatory, antioxidant, and immunomodulatory biomarkers, with some differences observed between patients given raw camel milk and boiled camel milk. Conclusion: Camel milk shows promise in improving social behaviors and certain biochemical markers in children with ASD, although the current meta-analysis did not document a significant statistical difference in CARS scores for the children studied. Future studies should focus on rigorous RCTs and larger sample sizes to substantiate these preliminary findings. [Open Vet J 2024; 14(9.000): 2441-2452]